Inhibition of browning agents in bisected protocorm-derived callus of pigeon orchid (Dendrobium crumenatum Swartz) - Paveena Kaewubon (Prince of Songkla University, 2016)
Thesis (Ph.D., (Biology))--Prince of Songkla University, 2015